Statistics from Space: Next-Generation Agriculture Production Information for Enhanced Monitoring of Food Security in Mozambique - Groundtruthing data collection and stakeholder engagement report - Centre of Excellence in Agri-Food Systems and Nutrition (International Food Policy Research Institute, 2025)
The Statistics from Space project (SFS) seeks to support the Government of Mozambique to produce and disseminate accurate crop production statistical data leveraging satellite remote-sensing data and artificial intelligence augmented analytics. The project, funded by the Government of the Republic of Korea (Ministry of Agriculture, Food and Rural Affairs; MAFRA), aims to provide the Mozambican Ministry of Agriculture and Rural Development with production estimates of major crops across three provinces namely Gaza, Manica and Zambezia in a sufficiently timely manner so that all market participants can use the information for decision-making.